Clinical, epidemiological, and drug resistance insights into HIV-positive patients in Meizhou, China - Liu, Xianhui; Patil, Sandip; Guo, Xuemin; Wen, Feiqiu; Zhang, Xianyan; Zhong, Zhixiong; Wang, Xinlu (Frontiers in Cellular and Infection Microbiology, 2024)
The acquired immunodeficiency syndrome (AIDS) epidemic, resulting from human immunodeficiency virus (HIV) infection, exhibits distinct regional characteristics. This study undertakes a retrospective analysis of the epidemiological and clinical features of 195 HIV-positive cases in Meizhou, China, from May 1, 2018 to December 31, 2019. Western blotting (WB) confirmed and assessed these cases. Notably, the majority of cases emanated from socio-economic groups with comparatively lower levels of education, with 80% being male. Strikingly, 90% of the cases were found to be in the middle to late stages of infection based on CD4+ T cell counts. Among the 30 different serum antibody profiles examined, reactivity with seven bands (p24, p31, gp41, p51, p66, gp120, and gp160) emerged as the most commonly observed WB pattern. The absence of specific bands, specifically p55 (17.44%), p39 (32.31%), and p17 (25.64%) were most frequent, with the detection frequency of p17 bands significantly reduced among cases in the AIDS and middle stages. An analysis of drug resistance genotypes indicated that, despite viral mutations conferring resistance to certain reverse transcriptase inhibitors, the first-line treatment regimen remained effective for patients in Meizhou. Notably, mutations resistant to protease inhibitors were infrequent (2.7%), suggesting that incorporating protease inhibitors into the treatment regimen may enhance therapeutic outcomes for local patients. These findings provide essential insights into the specific epidemiological patterns, serum antibody profiles, and drug resistance genotypes of HIV-infected patients in Meizhou. Significantly, this research contributes to the formulation of future treatment strategies tailored to the local context.